Feasibility and acceptability of frequent vaginal self-sampling at home by Rwandan women at high risk of urogenital tract infections. (29th January 2021) - Verwijs, Marijn C; Agaba, Stephen; Umulisa, Marie-Michele; van de Wijgert, Janneke H H M
Abstract : Objectives: To establish temporal links between vaginal microbiota (VMB) data and incident clinical events, frequent longitudinal vaginal sampling is required. Self-collection of swabs at the participant's home may be useful to avoid overburdening research clinics and participants. One-off vaginal self-sampling for STI or cervical cancer screening programmes has been shown to be feasible and acceptable to women in multiple studies, including in sub-Saharan Africa, but the feasibility and acceptability of frequent longitudinal vaginal sampling in the context of VMB sequencing studies is unknown. Methods: Twelve participants of a randomised clinical trial in Kigali, Rwanda, self-collected vaginal swabs three times a week for a month. We studied feasibility by comparing DNA concentrations, proportions of samples with >1000 16S rRNA amplicon sequencing reads and VMB composition outcomes of self-collected swabs with clinician-collected swabs. We evaluated the acceptability of self-collection using structured face-to-face interviews and a focus group discussion. Results: The participants collected vaginal swabs at 131 different time points. One woman stopped self-sampling after one try due to a social harm. All self-sampled swabs generated >1000 rRNA amplicon sequencing reads, and the DNA concentration of self-sampled swabs and clinician-sampled swabs did not differ significantly (Kruskal-Wallis p=0.484). Self-sampled and clinician-sampled swabs generated similar VMB composition data. Participants reported feeling very comfortable during self-sampling (11/12; 91.7%) and that self-sampling had become easier over time (12/12; 100%). They mentioned reduced travel time and travel costs as advantages of self-sampling at home. Conclusions: Frequent longitudinal vaginal sampling at home is feasible and acceptable to participants, even in the context of a low-resource setting, as long as adequate counselling is provided. Trial registration number: NCT02459665 .